Childbearing women's experiences of the maternity care system in Australia during the first wave of the COVID-19 pandemic. Issue 3 (May 2022) - Sweet, Linda; Wilson, Alyce N.; Bradfield, Zoe; Hauck, Yvonne; Kuliukas, Lesley; Homer, Caroline S.E.; Szabo, Rebecca A.; Wynter, Karen; Vasilevski, Vidanka
Abstract: Background: Substantial changes occurred in Australian healthcare provision during the COVID-19 pandemic to reduce the risk of infection transmission. Little is known about the impact of these changes on childbearing women. Aim: To explore and describe childbearing women's experiences of receiving maternity care during the COVID-19 pandemic in Australia. Methods: A qualitative exploratory design using semi-structured interviews was used. Women were recruited through social media and self-nominated to participate in an interview. Maximum variation sampling was used. Twenty-seven interviews were conducted with women from across Australia. Data was analysed thematically. Findings: Three primary themes and nine sub-themes emerged: 'navigating a changing health system' (coping with constant change, altered access to care, dealing with physical distancing restrictions, and missing care), 'desiring choice and control' (experiencing poor communication, making hard decisions, and considering alternate models of care), and 'experiencing infection prevention measures' (minimising the risk of exposure and changing care plans to minimise infection risk). Discussion: The substantial changes in care delivery for pregnant and postpartum women during the pandemic appear to have reduced woman-centred care. In most cases, care was perceived as impersonal and incomplete, resulting in a very different experience than expected; consequences included missing care. The presence of a known care provider improved women's sense of communication, choice, and control. Conclusion: This study provides unique insight into the experiences of childbearing women across Australia. The importance of respectful woman-centred care cannot be forgotten during a pandemic. The findings may inform future service planning during pandemics and disaster situations.